Detection of Trace Explosive Materials by Standoff Raman Spectroscopy System - Abdulzahraa, Haider G; Hadi, Naseer M; Mohammad, Mohammad R (Al-Nahrain Journal of Science, 2017)
Standoff Raman spectroscopy SRS technique is one of the most powerful technologies that can identify trace amount of explosive materials. The Raman scattered signal collected by reflective telescope and a spectrograph is used to analyze the Raman scattered light. In order to view the spectrum, the spectrograph is equipped with charge coupled device CCD detector which allows detection of very weak stokes line. In order to test the capability of SRS system of detecting explosives trace, detection of C4 and AN explosives have been achieved with limit of detection (LOD) about 20 µg for C4 and 40 µg for AN.